1982
DOI: 10.1002/jcp.1041130306
|View full text |Cite
|
Sign up to set email alerts
|

Growth and death of hela cells in the presence of caffeine

Abstract: Proliferation and death were measured in synchronously growing cultures of HeLa S3 cells during treatment with up to 30 mM caffeine. Changes in the number of colony-forming cells were determined by single-cell plating, while changes in the total number of cells were measured both by electronic counting and by monitoring cell division and physiological death cinemicrographically. At concentrations between 2 and 5 mM, cell killing occurs over several days during which the cells traverse the generation cycle once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…It was found that with 5 mM caffeine, 0.5-5 mM HOU give maximal killing; 0.1 mM is less effective. With 1 mM HOU, 5 and 10 mM caffeine are maximally effective, 3 or 20 mM less so, the latter presumably because of its large toxicity (by itselfl to G1 cells (Beetham and Tolmach, 1982b). Similar though less extensive measurements of the synergistic effect with cells treated in S indicate general agreement with the results of GI-initiated exposures.…”
Section: Age Dependencesupporting
confidence: 71%
See 2 more Smart Citations
“…It was found that with 5 mM caffeine, 0.5-5 mM HOU give maximal killing; 0.1 mM is less effective. With 1 mM HOU, 5 and 10 mM caffeine are maximally effective, 3 or 20 mM less so, the latter presumably because of its large toxicity (by itselfl to G1 cells (Beetham and Tolmach, 1982b). Similar though less extensive measurements of the synergistic effect with cells treated in S indicate general agreement with the results of GI-initiated exposures.…”
Section: Age Dependencesupporting
confidence: 71%
“…It has also been found to increase unpredictably the rate of DNA synthesis Painter, 1980). In addition, at concentrations between 5 and 15 mM, caffeine kills our line of HeLa cells if they are in S, but at higher concentrations it kills cells in G1 as well (Beetham and Tolmach, 1982b). It also induces mutations and chromosome aberrations (see Kihlman, 1977).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeine has long been known to induce a G1 delay in mammalian cells [65][66][67], and we showed that caffeineinduced ~75% inhibition of G1/S progression in diploid human fibroblast strains. ATM and p53 were not required as AT cells and cells expressing HPV16E6 to inactivate p53 also arrested in G1 when incubated in caffeine.…”
Section: Discussionmentioning
confidence: 72%
“…While caffeineinduced perturbations in mitosis and cell division are well documented (e.g. Kihlman, 1977;Beetham & Tolmach, 1982), and while caffeine may inhibit cell division in C. elegans, the developmental biology of this organism indicates this hypothesis to be untenable. Specifically, the increase in size throughout development is due largely to increase in cell size rather than cell number.…”
Section: Discussionmentioning
confidence: 97%